(untitled) (Conferencea, 2024)
In recent years, the economic growth dynamics of Uzbekistan have stabilized. This trend has a positive effect on the standard of living of the population. On the other hand, these two factors cause a constant increase in electricity consumption. Until 2030, the demand for electricity in the country is predicted to grow by about 6-7% per year. However, Uzbekistan is not ready for such a scenario. Because the existing capacities do not allow to fully satisfy the internal needs. If urgent measures are not taken, the problem of energy shortage will certainly be a hindrance to our development in the future.